Akad Murokab on the DSN-MUI Fatwa and its Effect on Islamic Bank Funding Products - Fatah, Dede Abdul; Muchtasib, Ach. Bakhrul; Rahmatullah, Indra; Soydan, Mustafa Zafer (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2022)
The study determines whether Islamic bank management understands hybrid contracts in the DSN-MUI funding fatwa and its influence on developing funding products in Islamic banks. The type of research used is normative juridical to examine the application of Islamic legal rules both at the methodological level (uṣul fiqh) and fiqh rules and at the product level (fiqh). The primary data of this study comes from the DSN-MUI fatwa and interviews to explore the understanding of Islamic bank management towards hybrid contracts in the DSN-MUI funding fatwa. This study indicates that from eight fatwas on DSN- MUI funding products, only fatwa No. 86 and 87 containing hybrid contracts. There are several theoretical frameworks, standards, and limitations (ḍawābiṭ) that the DSN-MUI has determined. The study also shows that the management of Islamic banks, generally, has understood the theoretical framework, standards and limitations of hybrid contracts on Islamic bank funding products only in textual concept. The textual understanding can increase the portfolio of funding products. This can be evidenced by the increasing portfolio of muḍārabah savings and income smoothing programs at Islamic banks.  Abstrak Penelitian ini mengkaji apakah manajemen bank syariah memahami kontrak hybrid dalam fatwa pendanaan DSN-MUI dan pengaruhnya terhadap pengembangan produk pendanaan di bank syariah. Metode yuridis normatif digunakan untuk mengkaji penerapan kaidah hukum Islam baik pada tataran metodologis (ushul fiqh) dan kaidah fikih maupun tataran produk (fikih). Data utama penelitian ini bersumber dari fatwa DSN-MUI dan wawancara untuk menggali pemahaman manajemen bank syariah terhadap multi akad pada fatwa pendanaan DSN-MUI. Penelitian ini menunjukan bahwa dari 8 fatwa produk pendanaan DSN-MUI hanya fatwa No. 86 dan 87 yang terdapat multi akad dengan beberapa kerangka teori, standar, dan batasan-batasan (ḍawābiṭ) yang telah ditentukan oleh DSN-MUI agar tidak terjeurumus pada multi akad yang dilarang. Penelitian ini juga menunjukan bahwa manajemen bank Syariah secara umum sudah memahami kerangka teori, standar dan batasan-batasan multi akad pada produk pendanaan bank Syariah pada konsep tekstual di mana dapat mempengaruhi peningkatan portofolio produk penadanaan. Hal ini dapat dibuktikan dengan meningkatnya portofolio tabungan mudharabah dan program income smoothing di bank Syariah.